Family caregiver’s willingness to care from the perspective of altruism - Li, Jun; Zhan, Jing-Chun; Xie, Cui-Hua; Han, Shao-Yong (Frontiers in Public Health, 2023)
The willingness of family members to take care of older relatives directly affects the quality of life of disabled older adults, so it is necessary to understand the status quo of willingness to care and its influencing factors. This has been extensively studied in other countries, but, it is rarely studied in China. Based on the theory of altruism, employing a unique sample from Shanghai, China in 2022, we attempt to reveal the influencing factors of the care willingness of family caregivers during the transition period.Methods: To measure caregiver burden and functional disability of the care recipient, we employ the Zarit Burden Interview (ZBI) and the Barthel Index respectively. Then we utilized the ordinary least squares (OLS) methodology and estimated four regression models. Models 1, 2, and 3 examined the impact of the variables of the care burden, responsibility and love, and the quality of the caregiver-care recipient relationship, respectively, on family caregivers' willingness to care. Model 4 was the full model. To testify whether the caregiver burden is likely to act as a mediator, path analysis was used, and the path was adjusted and verified.Results: According to the survey, in Shanghai, only half of the caregivers had a very high care willingness to care for disabled older relatives, while nearly one-tenth of the caregivers had a low willingness. It was found that it was the caregiver burden rather than the functional disability of older adults that harms family caregivers' willingness to care. Responsibility and caring out of love were positively related to care willingness. Relationship quality was the most important influencing factor, explaining 10.2% of the variance in care willingness. Path analysis demonstrated that responsibility, caring out of love, and relationship quality directly and through the mediation of caregiver burden indirectly affected care willingness.Our results revealed that reciprocal altruism presented by the quality of the caregiver-care recipient relationship has a significantly positive impact on family caregivers' willingness to care. In addition, the caregiver burden was found not only directly affect care willingness, but also acted as a mediator.